Alignment of Global Outcomes for Assessment and Accreditation - Ken Ryalls (Academic Chairpersons Conference Proceedings, 2016)
Influential higher education organizations aspire to measure different sets of global student outcomes, yet widespread agreement exists. This presentation centers on how IDEA's Student Ratings of Instruction Learning Objectives align with global outcomes from AAC&U's Value Rubric, Lumina's DQP, HLC's Criteria for Accreditation, and NSSE's Engagement Indicators.
Keywords: student outcomes; assessment; accreditation; learning objectives; global outcomes